A measurement method for the dual fuel coupling injection characteristics of the high-pressure natural gas and diesel co-direct injection engine. (April 2022) - Yang, Xiyu; Wang, Xiaoyan; Dong, Quan; Wei, Daijun; Zhou, Tanqing
Highlights: An innovative measurement method for a two-phase fuel transient flow rate in the same space–time dimension is proposed. A spray filter is designed to realize the space extraction of the target jet. The optimized jet baffle structure is proposed, which greatly improves the quality of the test signal. Further injection characteristics are obtained through the measurement. Abstract: This paper presents an innovative measurement method for a two-phase fuel transient flow rate in the same space–time dimension. Based on the jet momentum measurement, a spray filter is designed to realize the space extraction of the target jet. The optimized jet baffle structure is proposed, which greatly improves the quality of the test signal. Compared with the pressure–time method, this method has higher precision in the gas injection rate shape measurement and the recognition precision of gas injection beginning and ending moment. The coupling effect of two-phase fuel injection and the influence of different ambient pressures on injection performance can be studied by this method. The results show that the pilot diesel injection will cause more than 20% fluctuation of gas injection mass, and the ambient pressure can promote the gas needle opening, which will significantly affect the fuel injection mass of the engine.